I went to visit a friend one day (big book) - Ferguson, Virginia; Durkin, Peter Fleming, Leanne (Nelson Australia South Melbourne, Vic., 1994)
A rhyme, to be sung to the tune of "Here We Go Round the Mulberry Bush," about a friend who is busy with a different chore each day--until, at last, she has time to play